A call for a trauma-informed approach during compulsory care for enduring anorexia nervosa with combined PTSD – an autoethnographic perspective - Jennie Moberg (Journal of Eating Disorders)
Abstract Background Individuals with both anorexia nervosa (AN) and post-traumatic stress disorder (PTSD) often experience significant challenges in psychiatric inpatient care, particularly when coercive measures are used. While the comorbidity of AN and PTSD is well-documented, their interplay in the context of compulsory care and from a lived experience and trauma-informed perspective remains underexplored, despite its critical impact on treatment outcomes. This autoethnographic study aims to shed light on how coercion is experienced in this context, highlighting the need for a trauma-informed approach that acknowledges patients’ histories rather than solely viewing their behaviors as pathological. The Power Threat Meaning Framework (PTMF) provides a theoretical lens for understanding how trauma affects individuals with AN and PTSD, emphasizing the importance of viewing these conditions not just as symptoms to be treated but as survival strategies linked to broader trauma histories. Methods An autoethnographic approach was used to analyze blog posts, clinical notes, and diary entries from 2010 to 2019, focusing on experiences of AN, coercion, and trauma. Results One overarching theme, ‘Life in inpatient care’, and four subthemes emerged: (1) ‘Being sucked into the vortex of hunger’, (2) ‘Relapse no. 5 and admission procedure – state of emergency’, (3) ‘Encountering coercion and losing control – living in constant fear’, and (4) ‘Managing the aftermaths of eating’. Conclusions This autoethnography highlights the interplay between AN and PTSD in compulsory inpatient care, showing how AN served as a coping mechanism for trauma, with starvation as emotional avoidance. The PTMF framework challenges diagnostic-based models, viewing these behaviors as survival strategies rather than pathology. Key findings highlight the impact of coercive treatments such as forced feeding and restraint, which can intensify fear and retraumatization. A trauma-informed approach prioritizing trust, autonomy, and trauma acknowledgment is essential for effective, compassionate care. Recovery should go beyond renourishment to include psychological healing and body-self reintegration, emphasizing a holistic, patient-centered approach for improved treatment outcomes.